Mengatasi Perundungan Verbal Melalui Peran Guru PAI di SD Negeri 18 Karan Aur (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Islamic Religious Education teachers not only play a role in teaching religious knowledge but also hold significant responsibility in guiding, advising, motivating, and setting good examples for students. They can educate students through a religious approach, such as encouraging them to draw closer to Allah SWT, study and memorize the Al-Qur'an, and engage in other activities that have a positive impact, particularly on behavior. The purpose of this research is to determine the role of Islamic Religious Education teachers in addressing student bullying behavior. This study is qualitative research using a case study approach. The research subject is the Islamic Religious Education teacher at SD Negeri 18 Karan Aur. Data were collected through interviews, observation, and documentation studies. The results of the research indicate that: (1) The role of Islamic Religious Education teachers in overcoming students' verbal bullying behavior includes acting as educators, motivators, and role models; (2) There are supporting and inhibiting factors faced by Islamic Religious Education teachers in dealing with students' verbal bullying behavior. The supporting factors include the cooperation of the school principal and other teachers in addressing bullying behavior. Bullying should be addressed from an early age so that students feel comfortable and at ease while studying at school, ensuring a more secure future for them.
Keywords: Bullying; Role; Islamic Education Teacher